A partnership to eradicate rural poverty (IFAD RomeIT, 2005)
Details IFAD and OPEC Fund's efforts to eradicate rural poverty. Shows how they work in partnership to do this and also how they support agricultural research.
Keywords: POVERTY ALLEVIATION